Comparison of public value measurement frameworks - Ćwiklicki, Marek (Journal of Public Governance, 2016)
Fair methodology for public performance measurement is at present one of the most important issues, especially in terms of providing high quality services for citizens in an economic way. Setting Public Value at the front of performance measurement makes it possible to present the benefits of more broadly defined effects of administration activities. The research objective of the paper is to analyse and compare the frameworks for measuring public value. Analysis and comparison were applied to the identified public value measurement frameworks based on the literature review. These frameworks were described on the basis of the literature review, which was conducted using relevant books and journals and supported by materials available on the Internet. Six public value measurement frameworks were compared. They originated from Public Value or Value Analysis, conducted mostly in the last decade in the USA and the United Kingdom, as part of the New Public Management agenda. Measuring public value has entered its maturity phase. It has evolved from a general concept, to explaining the role of public managers, to more specific procedures for establishing countable results and the area of application was extended: from public to all kinds of organisations.